La modernidad del Lazarillo de Tormes - Garrido Ardila, Juan Antonio (Symposium, 2018)
Recent literary scholarship has revisited and reassessed the modernity of Don Quixote and, to a lesser extent, of Lazarillo de Tormes. This article substantiates Lazarillo’s place as a modern text in Spanish literature by means of a textual analysis in relation to the historical and philosophical contexts in which it was composed. This analysis of Lazarillo’s historical modernity examines the contemporary setting of the plot, the satire of institutions and of new legislation, and the insightful depiction of social classes and their lifestyles. The present study of Lazarillo’s philosophical modernity critiques its post-Medieval Weltanschuung, the modern subjectivity of its point of view, and the narrator’s acute disenchantment with the world. In conclusion, Lazarillo is presented as a literary masterpiece characterized by its portrayal of the post-Medieval society and philosophy that define modernity, and as a central milestone in the history of European literature published some five decades before Don Quixote.